THE IMPORTANCE OF CLASS DISCUSSION IN TEACHING A LANGUAGE AT THE SENIOR STAGE (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article discusses the importance of class discussion in teaching a language at the senior stage. The study examines how discussion-based activities improve students’ communicative competence, speaking fluency, critical thinking, and motivation. The article also analyzes the psychological and educational benefits of class discussions and suggests effective strategies for successful implementation in language classrooms. In modern educational systems, communicative methods have become central to language instruction, especially among senior students who already possess basic linguistic knowledge. The article emphasizes that discussion activities encourage active participation, collaboration, independent thinking, and real-life communication skills. Furthermore, the research highlights that discussion-based learning helps students overcome fear of speaking, increases confidence, and promotes learner autonomy. Effective classroom discussions also contribute to the development of intercultural competence and social interaction skills, which are essential in the globalized world. Therefore, the integration of discussion methods into language teaching practices is considered one of the most productive approaches for developing communicative competence and academic success at the senior stage.